Cal State East Bay Climate Action Plan 2018 - Karina Garbesi::::::; Jillian Buckholz::::::; Brett Meleg:::::: (2018)
The Climate Action Plan details how California State University, East Bay will achieve reducing its carbon footprint and the structures necessary for successful implementation on its campuses.